Cuentas por cobrar de la empresa REYBANPAC REY BANANO DEL PACIFICO C.L., de la ciudad de Guayaquil en el periodo 2022. - Miranda Viteri, Byron Steven (2024)
This case study focuses on the analysis of the control of accounts receivable in REYBANPAC REY BANANO DEL PACÍFICO C.L., located in the city of Guayaquil, during the period 2022. The importance of this research lies in its ability to provide an understanding insight into how effective accounts receivable management directly impacts the company's financial stability and corporate reputation, especially in a challenging economic context. By observing the significant increase in accounts receivable and its effect on the company's liquidity, the need to explore the policies and processes implemented for the recovery of these credits, as well as their influence on the company's overall profitability, was identified. Adopting a mixed methodology that combines qualitative and quantitative techniques, an interview was conducted with the general process’s supervisor and an exhaustive analysis of the company's financial statements was carried out. The results revealed notable growth in accounts receivable, driven by a strategy of easing credit terms to support customers during difficult economic times. Although this tactic contributed to an increase in credit sales, it also posed challenges for REYBANPAC's liquidity, leading the company to strengthen its credit policies and improve collection processes.